C∞ SOFT MANIFOLDS - Marziyeh Mostafavi (Journal of New Theory)
In this paper, we briefly recall several basic notions of soft sets and soft topological spaces and we continue investigating the properties of soft mappings, soft continuous mappings and soft homeomorphisms. We introduce and discuss the properties of the soft topological manifolds of dimension n and define C∞soft manifolds which will strengthen the foundations of the theory of soft geometry. We study restriction of a soft mapping and then define submanifolds